(untitled) (Minerva, 2019)
The article examines the emerging concept of mythos/myth in the context of early Greek historiography and mythography. The possibility of contesting traditional stories is a critical factor in this process, and is closely related to the efforts of writers to establish their authority. Herodotos’ practice is compared with that of the early mythographers, and though there are some broad similarities, there are crucial differences in their approach to religious matters. Herodotos’ personal scruples account for some of his well-known reticence about the gods, but also relevant is his attitude to the historian’s task, and his notion of how gods act in history. If mythographers attempt to historicise mythology, he quite remarkably attempts to demythologise history, separating the two but at the same time defining more profoundly than ever their true interconnections. This situation prompts some general thoughts on the relationship between Greek myth and ritual.